The Continuity Clinic Podcast Series of the Texas Tech MedCast: Delgado Module (Out of Print) - Betsy Jones; David Trotter; Lance Evans; Marbella Zumaya; German Nunez; Michael Ragain (Association of American Medical Colleges, 2009)
Abstract Introduction The Continuity Clinic is a collection of medical education podcast modules that focus on the developing relationship between student doctors and their patients. This series was designed for third-year medical students who are beginning their clinical years and are starting to gain experience in building meaningful relationships with their patients. Each module contains a series of patient vignettes that follows a specific student doctor and patient over the course of several months to a year. Each module focuses on demonstrating the effects of good- and poor-patient communication on the doctor-patient relationship, and teaches specific communication skills. Each of these modules was designed by an interdisciplinary team including physicians, educators, and behavioral scientists. Methods The specific module presented here is titled "Mr. Delgado," where students learn about communication and rapport building techniques in the context of Type 2 diabetes diagnosis and management. In this module, Heather (a third-year student) must help her patient, Mr. Delgado, deal with several psychosocial issues which effect his health status. Communication topics covered in these episodes include the use of open- and close-ended interview styles, application of the Stages of Change model, and the use of the concern/cutdown, anger, guilt, eye-opener (CAGE) alcohol screening tool. Each of the four vignettes contains an audio file of the doctor-patient interaction, and a study guide. Results While we do not currently have effectiveness data for the Delgado module, we have extensive student feedback on other vignettes in the series. In general, our data suggest a dose-response relationship between the number of podcasts students listen to and their cognitive test performance on related materials. Specifically, as students listen to more episodes within a series, their scores on cognitive tests of covered material increases. Further, our data suggest that students are generally satisfied with the series, and that they find them to be useful educational tools. Discussion We have found that our students frequently find it difficult or painful to listen to the student in the Delgado vignettes make serious communication mistakes. Our students expressed this discomfort by making statements like "I can't believe that she said that, I would never say that," and "Well, of course he was mad she is not communicating all that well." Exploring this discomfort with students has shown itself to be a rich and interesting way to talk about communication, rapport building, and emotional reactions to patients. Also, it is our hope that talking about these communication problems will encourage students to discuss communication mistakes they have made during their clinical education.